IMPROVEMENT OF AMLODIPINE CONTROL EFFICACY OVER HYPERTENSION USING FIXED COMBINATION OF PERINDOPRIL ARGININE AND AMLODIPINE - O. N. Kryuchkova; E. A. Itskova; U. A. Lutay; E. U. Turna; E. A. Kostyukova; T. V. Kucherenko (Российский кардиологический журнал)
Aim. To evaluate possibilities of hypertension control improvement using fixed combination of perindopril arginine and amlodipine.Material and methods. Totally 46 patients studied (25 men, 21 women of the age 53,6±4,3y.)with arterial hypertension 2-3 grade. All patients underwent ABPM with analysis of the following: mean 24-hour BP, velocity of morning SBP and DBP rise, BP variability of Ps BP (VPsBPd, VPsBPn).The criteria of inclusion were insufficient control over hypertension while using free combinations of ACE inhibitor or angiotensin II receptor blockers and diuretic or calcium channel blocker. To control arterial hypertension all patients were prescribed the fixed combination of perindopril arginine/amlodipine it standard dosage 10/5 mg (Prestans, "Les Laboratories Servier", France) with further possible increase of dosage up to 10/10 mg.Results. While receiving the therapy 84,7% patients reached "target" BP. Mean 24-hour SBP decreased from 139,24±1,8to 121,13+1,22 mmHg (p<0,05), DBP decreased from 84,51±2,08 to 73,14±1,4 (p<0,05), mean BP decreased from 103,07±1,56 to 87,66±1,13 (p<0,05). 24-hour variability of SBP significantly decreased from 15,28±0,72 to 10,21±0,42 (p<0,05), DBP from 13,46±0,72 to 10,72±0,31 (p<0,001). Values of VMR after the treatment also decreased. Before treatment VMR of SBP was 27±3,26 mmHg/hour, on therapy —15,3±5,04 mmHg/hour, (p<0,01); the same for DBP — VMR decreased from 23,6±2,37 mmHg/hour to 11±1,62mmHg, (p<0,01).Conclusion. The usage of combined perindopril arginine/amlodipine in patients with former uncontrolled arterial hypertension at the background of free chosen antihypertensive drugs combinations succeeded in the target BP values achievement in 84,7% cases. The reached control over BP was successful daily and during the night, as over variability of BP and velocity of morning BP rise. Usage of fixed combination of perindopril arginine/amlodipine was marked with good tolerability and high patients' compliance.